Kedudukan Hukum Aset Bekas Milik Asing/ Tionghoa Menurut Peraturan Menteri Keuangan Nomor: 62/PMK.06/2020 di Kementerian Keuangan Cq. Direktorat Jenderal Kekayaan Negara Cq. Kantor Wilayah Direktorat Jenderal Kekayaan Negara Sumatera Utara - Martini, Rita; Limbong, Dayat; Isnaini, Isnaini (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study examines the legal position of Foreign/Chinese-Owned Assets (ABMA/T). That there are 40 (forty) ABMA/T in Medan City. 15 (fifteen) have completed their legal status and 25 (twenty five) have not. Based on this, the formulation of the problems, among others, the settlement of ABMA/T whose legal status has not been determined, legal certainty for those who occupy/control the physical ABMA/T, and settlement of the obstacles faced by ABMA/T. The research method used is normative juridical with a statutory and conceptual approach. The data collection instruments used were interviews and literature studies/document studies, with descriptive data analysis qualitative analysis. The results of this study indicate that for the unresolved ABMA/T in the city of Medan, administrative and field research was carried out as well as discussion by the team. For ABMA/T occupied by a third party, a persuasive approach is carried out, it is explained how the settlement procedure is, if it is certified but not through the procedures that have been applied, a blocking registration is carried out. Settlement of ABMA/T constraints is carried out by completing administrative files by the team gradually and continuously, coordinating all parties, optimizing the performance of elements outside the Ministry of Finance, and harmonizing related legal regulations.